PENGALAMAN MENJADI IBU DI ERA DIGITAL: INTERPRETATIVE PEHNOMENOLOGICAL ANALYSIS - Rizky Rahmawati Khuzma; Yohanis Franz La Kahija (Faculty of Psychology, Diponegoro University, 2017)
The use of technology for children nowadays has been a common thing. Parents have facilitated their children who are still in the early age with personal gadget. The technology's use produces positive and negative impacts to the user. This research aims to identify the effect of the use of children technology to the mother. Meanwhile, the type of this research is qualitative with phenomenology study. The participants are mother with children who have known about gadget in the early age and have the personal gadget. For this study, the writer also used purposive sampling technique. The result shows that mother has introduced technology to the early age children. It is caused by the background of receiving gadget from the grandparents, job, and the trust in children. The use of gadget affects both negative and positive impact for mother and children. The positive impact for the children is helping them to study, to have entertaining media, and to settle down theirself whereas the negative is causing such an aggressive act, the decreasing of children's concentration and attention, and the difficulty of speaking. At the same time, the positive impact for the mother is helping them to take care of children, to communicate easier with children, and to make children staying at home. The negative impact felt by mother is that children put theirself as an object of aggressive act, the difficulty to gain children's attention, and the worry of personal gadget used by children.